2022
DOI: 10.3390/su14137868
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Ecological Patterns of Poyang Lake Wetland Landscape over the Last One Hundred Years Based on Historical Topographic Maps and Landsat Images

Abstract: Ecological pattern evolution of Poyang Lake wetland, the largest freshwater lake in China, is critical for regional ecological protection and sustainable development of migratory bird habitats; however, this information is still not fully explored. In this study, we quantitatively reconstructed the spatial distribution and landscape ecological pattern of Poyang Lake wetlands in three periods in the past 100 years based on the military topographic map in the 1930s and the Landsat satellite remote sensing image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…NPP is an important ecosystem service provided by Poyang Lake. Ye et al [22] observed that annual NPP shows a significant negative correlation with water inundation duration in Poyang Lake, and the correlation intensity is far greater than that of the other three influencing factors (air temperature, solar radiation, and precipitation) that control This study showed that there were many similarities in the spatial and temporal changes in the WO of Poyang Lake and Dongting Lake. For example, both experienced a decreasing trend in the mean WO (Figure 4) and hydrological connectivity (Figure 8).…”
Section: Ecological Impact Of Water Occurrence Changesmentioning
confidence: 57%
See 2 more Smart Citations
“…NPP is an important ecosystem service provided by Poyang Lake. Ye et al [22] observed that annual NPP shows a significant negative correlation with water inundation duration in Poyang Lake, and the correlation intensity is far greater than that of the other three influencing factors (air temperature, solar radiation, and precipitation) that control This study showed that there were many similarities in the spatial and temporal changes in the WO of Poyang Lake and Dongting Lake. For example, both experienced a decreasing trend in the mean WO (Figure 4) and hydrological connectivity (Figure 8).…”
Section: Ecological Impact Of Water Occurrence Changesmentioning
confidence: 57%
“…NPP is an important ecosystem service provided by Poyang Lake. Ye et al [22] observed that annual NPP shows a significant negative correlation with water inundation duration in Poyang Lake, and the correlation intensity is far greater than that of the other three influencing factors (air temperature, solar radiation, and precipitation) that control NPP. In this study, we observed that there was a significantly negative correlation between the mean WO and NPP in Poyang Lake.…”
Section: Ecological Impact Of Water Occurrence Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when farmland, dykes, islands, etc, are distributed in or around the lake, the integrality of the lake is destroyed, and the fragmented lake will weaken the connection between the parts. For example, the fragmentation of the lake area of Poyang Lake has increased due to the large area of cultivated land reclamation [18]. Due to the artificial construction of dikes and bridges, East Lake was divided into several sub-lakes [19].…”
Section: Introductionmentioning
confidence: 99%